2003
DOI: 10.1096/fj.02-1008com
|View full text |Cite
|
Sign up to set email alerts
|

Histamine enhances TGF‐β1‐mediated suppression of Th2 responses

Abstract: Susceptibility of T cells to TGF-beta1 produced by regulatory T cells has an important impact on the induction and maintenance of peripheral tolerance and therefore on the development of autoimmunity, cancer, and allergy. Histamine not only mediates the deleterious effects of allergic reactions, it can also modulate the Th1/Th2 cell balance. We demonstrate that histamine dose-dependently enhanced TGF-beta1-mediated suppression and TGF-beta1 responsiveness of CD4+ T cells. This effect was mediated by the histam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 38 publications
(54 reference statements)
0
51
0
Order By: Relevance
“…Increased IL-10 production in both DCs and T cells may account for an important regulatory mechanism in the control of inflammatory functions through histamine. In accordance with this phenomenon, it has recently been demonstrated that histamine supports the suppressive effect of TGF-␤ on T cells via HR2 [189]. Th2 cells are more affected by histamineenhanced TGF-␤ suppression, which is particularly important for the regulation of allergen-specific T cells in allergic immune responses.…”
Section: P R O O Fmentioning
confidence: 57%
See 1 more Smart Citation
“…Increased IL-10 production in both DCs and T cells may account for an important regulatory mechanism in the control of inflammatory functions through histamine. In accordance with this phenomenon, it has recently been demonstrated that histamine supports the suppressive effect of TGF-␤ on T cells via HR2 [189]. Th2 cells are more affected by histamineenhanced TGF-␤ suppression, which is particularly important for the regulation of allergen-specific T cells in allergic immune responses.…”
Section: P R O O Fmentioning
confidence: 57%
“…In addition, histamine induces IL-10 production by Th2 cells [188]. Furthermore, histamine enhances the suppressive activity of TGF-␤ on T cells [189]. All three of these effects are mediated via HR2, which is relatively highly expressed on Th2 cells and suppresses IL-4 and IL-13 production and T-cell proliferation [49].…”
Section: Clinical Evidence For T-regulatory Function Of Histamine Recmentioning
confidence: 99%
“…Increased IL-10 production in both DC and T cells may account for an important regulatory mechanism in the control of inflammatory functions through histamine. In accordance with this phenomenon, it has recently been demonstrated that histamine supports the suppressive effect of TGF-b on T cells via HR2 (195). The Th2 cells are more affected by histamine-enhanced TGF-b suppression, which is particularly important for the regulation of allergenspecific T cells in allergic immune responses.…”
Section: Camp Stimulating G-protein Coupled Receptors In Peripheral Tmentioning
confidence: 57%
“…In addition, histamine induces IL-10 production by Th2 cells (194). Furthermore, histamine enhances the suppressive activity of TGF-b on T cells (195). All three of these effects are mediated via HR2, which is relatively highly expressed on Th2 cells and suppresses IL-4 and IL-13 production and T-cell proliferation (40).…”
Section: Clinical Evidence For T Regulatory Function Of Histamine Recmentioning
confidence: 99%
“…In addition, histamine induces IL-10 production by Th2 cells [55]. Furthermore, histamine enhances the suppressive activity of TGF-β on T cells [58]. All of these three effects are mediated via HR2, which is relatively highly expressed on Th2 cells and suppresses IL-4 and IL-13 production and T cell proliferation [53].…”
Section: Regulation Of Immune Responsementioning
confidence: 99%